(untitled) (Indian Journal of Arid Horticulture, 2025)
Analysis of Aonla leaf samples showed that sulphur and manganese were found low in range whereas nitrogen, phosphorus, potassium, calcium and zinc were found low to medium in range. The magnesium, iron and copper were found in sufficient in range. The overall mean values of nitrogen, phosphorus, potassium, calcium, magnesium and sulphur were 0.842, 0.105, 0.384, 0.503, 0.387 and 0.0417 per cent, respectively whereas overall mean values of copper, manganese, zinc and iron were 9.34, 9.15, 10.04 and 120.66 mg kg, respectively in aonla orchards.